Efficacy of the Mosquitofish, Gambusia affinis (Baird and Girard) in the Control of Anopheles and Culex Mosquito larvae in Sennar State, Sudan - Salim, Omer A. A.; Hassan, Ahmed E. M.; Bala, Adil E.A. (University of Khartoum Journal of Agricultural Sciences, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*190.46px); top: calc(var(–scale-factor)*265.03px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.941156);" role="presentation">This <span dir="ltr" style="left: calc(var(–scale-factor)*219.25px); top: calc(var(–scale-factor)*265.03px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.960595);" role="presentation">laboratory and <span dir="ltr" style="left: calc(var(–scale-factor)*300.34px); top: calc(var(–scale-factor)*265.03px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.947264);" role="presentation">semi-field <span dir="ltr" style="left: calc(var(–scale-factor)*356.44px); top: calc(var(–scale-factor)*265.03px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.877032);" role="presentation">studies <span dir="ltr" style="left: calc(var(–scale-factor)*397.33px); top: calc(var(–scale-factor)*265.03px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.893656);" role="presentation">were <span dir="ltr" style="left: calc(var(–scale-factor)*427.92px); top: calc(var(–scale-factor)*265.03px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.872458);" role="presentation">designed <span dir="ltr" style="left: calc(var(–scale-factor)*477.95px); top: calc(var(–scale-factor)*265.03px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.9336);" role="presentation">to <span dir="ltr" style="left: calc(var(–scale-factor)*129.86px); top: calc(var(–scale-factor)*278.83px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.956138);" role="presentation">explore the larvivorous potential of <span dir="ltr" style="left: calc(var(–scale-factor)*309.05px); top: calc(var(–scale-factor)*278.83px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.938972);" role="presentation">Gambusia affinis <span dir="ltr" style="left: calc(var(–scale-factor)*397.27px); top: calc(var(–scale-factor)*278.83px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.951331);" role="presentation">and ways this fish <span dir="ltr" style="left: calc(var(–scale-factor)*129.86px); top: calc(var(–scale-factor)*292.63px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.914564);" role="presentation">might be employed in an ongoing Sennar state mosquito control program. <span dir="ltr" style="left: calc(var(–scale-factor)*129.86px); top: calc(var(–scale-factor)*306.43px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.926641);" role="presentation">The present experiments were conducted on <span dir="ltr" style="left: calc(var(–scale-factor)*354.67px); top: calc(var(–scale-factor)*306.43px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.98455);" role="presentation">G. affinis <span dir="ltr" style="left: calc(var(–scale-factor)*405.91px); top: calc(var(–scale-factor)*306.43px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.912255);" role="presentation">feeding patterns. <span dir="ltr" style="left: calc(var(–scale-factor)*129.86px); top: calc(var(–scale-factor)*320.23px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.9);" role="presentation">The mean number of larvae consumed by <span dir="ltr" style="left: calc(var(–scale-factor)*332.71px); top: calc(var(–scale-factor)*320.23px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.951698);" role="presentation">G. affinis <span dir="ltr" style="left: calc(var(–scale-factor)*380.83px); top: calc(var(–scale-factor)*320.23px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.908716);" role="presentation">was 132 larvae during <span dir="ltr" style="left: calc(var(–scale-factor)*129.86px); top: calc(var(–scale-factor)*334.03px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.964794);" role="presentation">24 hours. Additionally, <span dir="ltr" style="left: calc(var(–scale-factor)*247.01px); top: calc(var(–scale-factor)*334.03px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.972071);" role="presentation">G. affinis <span dir="ltr" style="left: calc(var(–scale-factor)*296.81px); top: calc(var(–scale-factor)*334.03px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.922013);" role="presentation">had a tendency to feed on early instars <span dir="ltr" style="left: calc(var(–scale-factor)*129.86px); top: calc(var(–scale-factor)*347.83px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.990908);" role="presentation">than the late ones under both laboratory and semi-field conditions in <span dir="ltr" style="left: calc(var(–scale-factor)*129.86px); top: calc(var(–scale-factor)*361.63px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.976993);" role="presentation">Sennar state. The percentages of larval consumption were 98% (±4), <span dir="ltr" style="left: calc(var(–scale-factor)*129.86px); top: calc(var(–scale-factor)*375.43px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.954723);" role="presentation">86.2% (±13.6), 77.4% (±7.3) and 63.6% (±32.5) for the 1<span dir="ltr" style="left: calc(var(–scale-factor)*416.11px); top: calc(var(–scale-factor)*372.91px); font-size: calc(var(–scale-factor)*8.04px); font-family: sans-serif; transform: scaleX(0.811382);" role="presentation">st<span dir="ltr" style="left: calc(var(–scale-factor)*421.51px); top: calc(var(–scale-factor)*375.43px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.989347);" role="presentation">, 2<span dir="ltr" style="left: calc(var(–scale-factor)*434.71px); top: calc(var(–scale-factor)*372.91px); font-size: calc(var(–scale-factor)*8.04px); font-family: sans-serif; transform: scaleX(0.964286);" role="presentation">nd<span dir="ltr" style="left: calc(var(–scale-factor)*442.87px); top: calc(var(–scale-factor)*375.43px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.989347);" role="presentation">, 3<span dir="ltr" style="left: calc(var(–scale-factor)*456.07px); top: calc(var(–scale-factor)*372.91px); font-size: calc(var(–scale-factor)*8.04px); font-family: sans-serif; transform: scaleX(1.00909);" role="presentation">rd<span dir="ltr" style="left: calc(var(–scale-factor)*462.82px); top: calc(var(–scale-factor)*375.43px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.921935);" role="presentation">, and 4<span dir="ltr" style="left: calc(var(–scale-factor)*135.86px); top: calc(var(–scale-factor)*386.71px); font-size: calc(var(–scale-factor)*8.04px); font-family: sans-serif; transform: scaleX(0.954549);" role="presentation">th <span dir="ltr" style="left: calc(var(–scale-factor)*147.62px); top: calc(var(–scale-factor)*389.25px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.952971);" role="presentation">instars, respecti`vely. The percentage of larvae consumed of varied <span dir="ltr" style="left: calc(var(–scale-factor)*129.86px); top: calc(var(–scale-factor)*403.05px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.934433);" role="presentation">instars was 87.4% (±21.8). Moreover, total consumption of the immature <span dir="ltr" style="left: calc(var(–scale-factor)*129.86px); top: calc(var(–scale-factor)*416.85px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.943783);" role="presentation">stages of mosquito larvae can be achieved as the number of <span dir="ltr" style="left: calc(var(–scale-factor)*437.47px); top: calc(var(–scale-factor)*416.85px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.88079);" role="presentation">Anopheles <span dir="ltr" style="left: calc(var(–scale-factor)*129.86px); top: calc(var(–scale-factor)*430.65px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.893758);" role="presentation">larvae <span dir="ltr" style="left: calc(var(–scale-factor)*167.05px); top: calc(var(–scale-factor)*430.65px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.877832);" role="presentation">consumed <span dir="ltr" style="left: calc(var(–scale-factor)*223.66px); top: calc(var(–scale-factor)*430.65px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.86747);" role="presentation">ranged <span dir="ltr" style="left: calc(var(–scale-factor)*264.09px); top: calc(var(–scale-factor)*430.65px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.878501);" role="presentation">between <span dir="ltr" style="left: calc(var(–scale-factor)*311.96px); top: calc(var(–scale-factor)*430.65px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.911379);" role="presentation">46.7% <span dir="ltr" style="left: calc(var(–scale-factor)*350.95px); top: calc(var(–scale-factor)*430.65px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.863568);" role="presentation">and <span dir="ltr" style="left: calc(var(–scale-factor)*376.26px); top: calc(var(–scale-factor)*430.65px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.912516);" role="presentation">100% <span dir="ltr" style="left: calc(var(–scale-factor)*412.24px); top: calc(var(–scale-factor)*430.65px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.878565);" role="presentation">(mean <span dir="ltr" style="left: calc(var(–scale-factor)*450.27px); top: calc(var(–scale-factor)*430.65px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.914061);" role="presentation">72.68% <span dir="ltr" style="left: calc(var(–scale-factor)*129.86px); top: calc(var(–scale-factor)*444.45px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.989414);" role="presentation">±20.04) and of <span dir="ltr" style="left: calc(var(–scale-factor)*212.21px); top: calc(var(–scale-factor)*444.45px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.91369);" role="presentation">Culex <span dir="ltr" style="left: calc(var(–scale-factor)*246.05px); top: calc(var(–scale-factor)*444.45px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.962326);" role="presentation">larvae between 54.2% and 100% (mean 86.7% <span dir="ltr" style="left: calc(var(–scale-factor)*129.86px); top: calc(var(–scale-factor)*458.25px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.921065);" role="presentation">±20.27). This study suggests that <span dir="ltr" style="left: calc(var(–scale-factor)*296.81px); top: calc(var(–scale-factor)*458.25px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.974363);" role="presentation">G, affinis <span dir="ltr" style="left: calc(var(–scale-factor)*346.99px); top: calc(var(–scale-factor)*458.25px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.961035);" role="presentation">could be a useful tool in the <span dir="ltr" style="left: calc(var(–scale-factor)*129.86px); top: calc(var(–scale-factor)*472.05px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.942325);" role="presentation">ongoing Sennar state vector control program. Further studies should be <span dir="ltr" style="left: calc(var(–scale-factor)*129.86px); top: calc(var(–scale-factor)*485.85px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.928278);" role="presentation">performed to assess the ecology, seasonality and to be conducted under <span dir="ltr" style="left: calc(var(–scale-factor)*129.86px); top: calc(var(–scale-factor)*499.65px); font-size: calc(var(–scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.878435);" role="presentation">large scale